Multicenter comparison of laboratory performance in cytomegalovirus and Epstein–Barr virus viral load testing using international standards. (13th November 2014) - Rychert, Jenna; Danziger‐Isakov, Lara; Yen‐Lieberman, Belinda; Storch, Gregory; Buller, Richard; Sweet, Stewart C.; Mehta, Aneesh K.; Cheeseman, Jennifer A.; Heeger, Peter; Rosenberg, Eric S.; Fishman, Jay A.
Abstract Background Infections with cytomegalovirus (CMV) and Epstein–Barr virus (EBV) remain important in solid organ transplantation. Quantitative viral nucleic acid testing is a major advance to patient management. These assays are limited by a lack of standardization, resulting in viral load measurements that differ among clinical laboratories. The variability in viral load measurements makes interpretation of multicenter clinical trials data difficult. This study compares the current practices in CMV and EBV viral load testing at four large transplant centers participating in multicenter Clinical Trials in Organ Transplantation and the Clinical Trials in Organ Transplantation in Children (CTOT and CTOTC). Methods Viral load testing was performed on well‐defined viral preparations according to standard operating procedures at each site. Results Among centers, CMV viral load testing was accurate compared to WHO International Standards and within acceptable variation for this testing method. Epstein–Barr virus viral load data were more variable and less accurate despite the use of international standards. Conclusions These data suggest that comparison of CMV, but not EBV, viral load measurements at these sites is possible using current assays and control standards. Standardization of these assays is facilitated using the WHO International Standards and will allow comparison of viral load results among transplant centers. Assay standardization must be performed prior to initiation of multicenter trials.